Du nulle part au partout : l’utopie de Wittig pour changer le présent et l’avenir - Kate Robin (Temporalités)
Though inspired by the revolutionary currents of the 1970s, writer Monique Wittig travels beyond temporal constraints. Culture is recreated, nourished by real or invented antiquity and prehistory. Such trans-temporal travel is common among feminist writers, it already inspired Christine de Pizan in the 15th century. Christine assembled a population of women from the past, present and future into the “City of Ladies”, where they could live together without spatial or temporal constraints. On the whole, feminist literary utopias are interested in questions of time and its reinvention in a cyclical and not linear form. Thus the symbol of the circle is used to structure Wittig’s writings, most clearly in Les Guérillères. This “epic” asserts a chronology, but not one of clocks and calendars. Such utopian writers link past and future, affording immediate and easy communication between the ages. The present, polluted by hierarchy and domination, is secondary in its everyday manifestations, but primordial in the sense that every aspect of literary creation is wholly dedicated to the constant and immediate improvement of our human condition.